Steroid-Refractory Gut Graft-Versus-Host Disease: What We Have Learned From Basic Immunology and Experimental Mouse Model - Song, Qingxiao; Nasri, Ubaydah; Zeng, Defu (Frontiers in Immunology, 2022)
Intestinal graft-versus-host disease (Gut-GVHD) is one of the major causes of mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). While systemic glucocorticoids (GCs) comprise the first-line treatment option, the response rate for GCs varies from 30% to 50%. The prognosis for patients with steroid-refractory acute Gut-GVHD (SR-Gut-aGVHD) remains dismal. The mechanisms underlying steroid resistance are unclear, and apart from ruxolitinib, there are no approved treatments for SR-Gut-aGVHD. In this review, we provide an overview of the current biological understanding of experimental SR-Gut-aGVHD pathogenesis, the advanced technology that can be applied to the human SR-Gut-aGVHD studies, and the potential novel therapeutic options for patients with SR-Gut-aGVHD.